Advances in digital document processing and retrieval (Statistical science and interdisciplinary research Vol. 13) - Chaudhuri, Bidyut Baran; Parui, Swapan Kumar (Platinum jubilee series, 2014)
Suitable for both students and researchers working on various aspects of document image analysis and recognition problems, this title covers such topics as: Going beyond the Myth of Paperlessness, The Role of Document Image Analysis in Trustworthy Elections as well as Word Recognition for Museum Index Cards with SNT-Grid.